Effectiveness of low-intensity aerobic exercise with assisted bicycle exercises on quality of life and lung functions in du-chenne muscular dystrophy - D, Anandan; V, Anandh; R, Arunachalam; B, ARUN; Krishnan Vasanthi3, Rajkumar (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Duchenne muscular dystrophy (DMD) is an X-linked recessive disorder caused by abnormalities in the dystrophin gene that affects one in every 3,500 males. In India, approximately 0.8 million were involved. Management is usually multidirectional and more focused on improving the quality of life (QOL), not mortality. Physiotherapy and exercise are an integral part of the management of DMD. Since there were no recommended exercises for DMD, there is a need to create an exercise protocol that improves the QOL. Low-intensity aerobic exercises are highly recommended for older people and are found effective. Objective: The study aimed to identify the effectiveness of low-intensity aerobic exercise with assisted bicycle exercises on QOL and lung functions in DMD. Methods: A randomized controlled trial was conducted at the Institute of Muscular Dystrophy and Research Centre, Jeevan Foundation, Veeravanalur, Tirunelveli Dist. Tamil Nadu, India. The institute has around 200 children with DMD. This study selected 34 children based on the criteria. I, the children, were provided with low-intensity aerobic exercise for seventeen children. Group II provided the children with assisted bicycle exercises for seventeen children. Both groups received exercises for 60 minutes and deep diaphragmatic breathing for 10 minutes. All are given a home program to the children. The total study duration is ten weeks. Results: Data were analysed following the assessment of Quality of life using DMD QoL and the Lung function using a spirometer (FVC, FEV1, FEV1/VC). All the data were collected on day 1, every two months. Parametric tests were used to compare the outcome measures. The student t value for the DMD QOL is 9.66 with p <0.001, the spirometry values of FEV1 are 7.67 with p< 0.001, and FVC is 14.78 with p < 0.001, respectively, and FEV1/VC is 10.81 with p < 0.001. Conclusion: This study concluded that low-intensity aerobic exercises and assisted bicycle training improve the QOL and lung functions. On comparing the interventions, it was found that low-intensity aerobic exercises are better improved than the assisted bicycle group.